Latent Herpes Simplex Virus Infections in Sensory Ganglia of Mice After Topical Treatment with Adenine Arabinoside and Adenine Arabinoside Monophosphate - Klein, Richard J. (1977)
Adenine arabinoside (Ara-A) and Ara-A monosphosphate (Ara-AMP) ointments were able to prevent the fatal outcome of herpes simplex virus (HSV)-induced skin infection of the lumbosacral area in hairless mice. Ara-A and Ara-AMP had no irritating effect on the skin, but in a number of animals a protracted healing time of the skin lesions after the treatment was observed. The compounds conferred only a partial protection against the establishment of latent HSV infection in the spinal root ganglia of the treated animals. The immune response, as judged from levels of HSV-specific neutralizing serum antibody titers, was not impaired by the antiviral treatment.